Penerapan Hydrogel dan Antimicrobial Dressing terhadap Penyembuhan Luka dan Sensasi Perifer pada Pasien Gangrene Pedis - Karina, Grashiva Putri; Sari, Eka Afrima; Harun, Hasniatisari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Gangrene is one of Diabetes Mellitus (DM) complication causing tissue death in wound and decreased peripheral sensation. Priority management of gangrene is through tissue reperfusion and wound care with modern dressing to enhance healing and increase periphery circulation. This research aimed to report wound healing progress and peripheral sensation gangrene in a patient who was given hydrogel and antimicrobial dressing. Research design used a descriptive case study approach. Sample involved one inpatient in West Java regional public hospital who was diagnosed with gangrene, had necrotic wounds, and poor peripheral perfusion, currently treated with modern dressing hydrogel and antimicrobial dressing. The instrument used is Bates Jensen Wound Assessment Tools (BJWAT), lowest score shows significant wound healing progress. Decreasing wound healing score using BJWAT questionnaire from 41 to 29, peripheral sensation (+), and monofilament score from 0/9 to 5/9 after the intervention. Modern dressing improved wound healing and peripheral sensation in gangrene pedis patient. Thus, it is expected to examine effectiveness of hydrogel and antimicrobial dressings on healing scores and peripheral sensation in gangrene pedis patients more extensively.